Anatomical and Physiological Responses of Citrus Trees to Varying Boron Availability Are Dependent on Rootstock - Mesquita, Geisa L.; Zambrosi, Fernando C. B.; Tanaka, Francisco A. O.; Boaretto, Rodrigo M.; Quaggio, José A.; Ribeiro, Rafael V.; Mattos, Dirceu (Frontiers in Plant Science, 2016)
In Citrus, water, nutrient transport and thereby fruit production, are influenced among other factors, by the interaction between rootstock and boron (B) nutrition. This study aimed to investigate how B affects the anatomical structure of roots and leaves as well as leaf gas exchange in sweet orange trees grafted on two contrasting rootstocks in response to B supply. Plants grafted on Swingle citrumelo or Sunki mandarin were grown in a nutrient solution of varying B concentration (deficient, adequate, and excessive). Those grafted on Swingle were more tolerant to both B deficiency and toxicity than those on Sunki, as revealed by higher shoot and root growth. In addition, plants grafted on Sunki exhibited more severe anatomical and physiological damages under B deficiency, showing thickening of xylem cell walls and impairments in whole-plant, leaf-specific hydraulic conductance and leaf CO2 assimilation. Our data revealed that trees grafted on Swingle sustain better growth under low B availablitlity in the root medium and still respond positively to increased B levels by combining higher B absorption and root growth as well as better organization of xylem vessels. Taken together, those traits improved water and B transport to the plant canopy. Under B toxicity, Swingle rootstock would also favor plant growth by reducing anatomical and ultrastructural damage to leaf tissue and improving water transport compared with plants grafted on Sunki. From a practical point of view, our results highlight that B management in citrus orchards shall take into account rootstock varieties, of which the Swingle rootstock was characterized by its performance on regulating anatomical and ultrastructural damages, improving water transport and limiting negative impacts of B stress conditions on plant growth.